The establishment of inter-municipal cooperation: the case of a polycentric post-socialist region. Issue 1 (2nd January 2020) - Osman, Robert; Šerý, Ondřej; Alexandrescu, Filip; Malý, Jiří; Mulíček, Ondřej
ABSTRACT: The paper deals with the process of establishing inter-municipal cooperation among towns, particularly among towns in a polycentric settlement system. Emphasis is on the specific temporal context of transition from a central administration to a decentralized form. For a more detailed analysis, the territory of the eastern part of Pardubice region, Czech Republic was chosen as the study area. Our research question therefore aims at the mechanisms of cooperation experimented with by the representatives of individual towns and it reads: "Which forms of inter-municipal cooperation can capitalize on a polycentric settlement system following the dismantling of the socialist centralized governance system?" To answer this question, semi-structured interviews were conducted with authorities of towns of the area. Based on the analysis of interviews, we show four distinct stages in establishing mutual cooperation were determined: stakes, emerging border areas, connecting projects and joint territory management. They are not stages in terms of discrete periods of time, but phases in a process of getting new experience with cooperation among municipalities. Findings are that a new strategic action field needs to be established in order to achieve a form of inter-municipal cooperation that would enable to gain the benefits of a polycentric post-socialist region.